The Memories of Soviet Era in Contemporary Lithuania: Ambivalence or Nostalgia? - Šutinienė, Irena (Sociologija. Mintis ir veiksmas, 2013)
The collective memories of Soviet era of Lithuanian adult population are analysed in the article. The analysis is based on the data of representative sociological survey, conducted by company „Baltijos tyrimai“ in 2012. The analysis reveals the ambivalence of the memories of Soviet era prevailing in popular memory: people express positive attitudes towards many aspects the Soviet era everyday life and simultaneously evaluate negatively political aspects of the Soviet regime. The Soviet era everyday is presented in people‘s memories as „apolitical“ and separated from political domain. The connections between attitudes towards Soviet past and contemporary contexts (attitudes towards the outcomes of democratization and indicators of social and economical position) reveal, that the memories of Soviet era are structured by generations in a great degree; there are also slight relations between positive (and nostalgic) memories of Soviet past and the social contexts of marginalization as well as feelings of marginalization. The slight relations of the memories of Soviet era to the contemporary social contexts and attitudes towards outcomes of democratization indicate, that positive memories of Soviet past are only partly nostalgic and are influenced by many other, among them individual, factors.